2023
DOI: 10.1128/jcm.00569-23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Qvella FAST System and the FAST-PBC cartridge for rapid species identification and antimicrobial resistance testing directly from positive blood cultures

Issa Sy,
Nina Bühler,
Sören L. Becker
et al.

Abstract: Blood culture diagnostics require rapid and accurate identification (ID) of pathogens and antimicrobial susceptibility testing (AST). Standard procedures, involving conventional cultivation on agar plates, may take up to 48 hours or more until AST completion. Recent approaches aim to shorten the processing time of positive blood cultures (PBC). The FAST System is a new technology, capable of purifying and concentrating bacterial/fungal pathogens from positive blood culture media and producing a bacterial suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The recently developed FAST system, used here on an experimental basis, allows identification and AST to be performed directly from broth cultures by removing cellular materials, proteins and other interfering substances that may be found in broth. Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13–17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87–96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13–18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recently developed FAST system, used here on an experimental basis, allows identification and AST to be performed directly from broth cultures by removing cellular materials, proteins and other interfering substances that may be found in broth. Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13–17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87–96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13–18].…”
Section: Discussionmentioning
confidence: 99%
“…Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13–17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87–96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13–18]. Not only has the FAST system been shown to be highly accurate, it has also been shown by other studies to significantly reduce workflow time [17, 18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation